A Survey of Existing Approaches for Computer Aided Diagnosis of Cancer - N., V.S.S.K. Suman; K. , Senthil Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Cancer is a deadly disease in which abnormal cells divide uncontrollably and destroy body tissue. It has various diagnosis techniques which are limited to only to some types of cancer. These diagnosis techniques have limited efficiency and do not guarantee the patient’s life. We plan diagnosis of this deadly disease at the initial stage itself. We take the patient’s medical records and gene data and look for cancer causing mutations(driver) and separate the other mutations (passengers).Thus we classify the gene and detect the mutations so that any patient with harmful mutations are potentially risk patients and thus are given treatment.